PENTINGNYA MANAJEMEN STRATEGI DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MELALUI TITIK PENJUALAN UNIK PADA PLATFORM E-COMMERCE MARKETPLACE SHOPEE, TOKOPEDIA DAN LAZADA DI BANYUWANGI, JEMBER, SITUBONDO DAN BONDOWOSO - Wirawan, Soni; Syahputra, Hendra; Minullah, Minullah (Relawan Jurnal Indonesia, 2025)
This study aims to analyze the influence of strategic management and brand awareness on purchasing decisions directly and indirectly through unique selling points in the context of e-commerce. By focusing on users of several marketplace applications in the former Besuki Residency which includes the regencies of Banyuwangi, Bondowoso, Jember and Situbondo. This study adopts a non-probability sampling method with a quota sampling technique to determine a sample of 200 users. Path analysis was carried out using the IBM AMOS program after the data was tested for validity and reliability with SPSS. The results of the study indicate that both strategic management and brand awareness have a positive and significant influence on unique selling points and purchasing decisions, in addition, unit selling points have an indirect effect on strategic management and brand awareness on purchasing decisions. These findings are expected to provide practical insights for e-commerce business actors in designing attractive and sustainable marketing strategies, and emphasize the importance of building strong brand recognition in the face of increasingly tight e-commerce industry competition